2011
DOI: 10.1002/bem.20712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct electric current on Herpetomonas samuelpessoai: An ultrastructural study

Abstract: The literature shows that the effects of direct electric currents on biological material are numerous, including bactericidal, fungicidal, parasiticidal, and anti-tumoral, among others. Non-pathogenic trypanosomatids, such as Herpetomonas samuelpessoai, have emerged as important models for the study of basic biological processes performed by a eukaryotic cell. The present study reports a dose-dependent anti-protozoan effect of direct electric treatment with both cathodic and anodic current flows on H. samuelpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Previous studies developed with direct electric current indicated the importance of pH variation in tumoral [Veiga et al, ; Cury et al, ; Holandino et al, ] and non‐tumoral damage [Gomes et al, , ]. For that reason, pH variation was registered with the same values of electric charge previously evaluated in cell viability experiments.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Previous studies developed with direct electric current indicated the importance of pH variation in tumoral [Veiga et al, ; Cury et al, ; Holandino et al, ] and non‐tumoral damage [Gomes et al, , ]. For that reason, pH variation was registered with the same values of electric charge previously evaluated in cell viability experiments.…”
Section: Resultsmentioning
confidence: 89%
“…In the present work, DC effects on C. albicans were evaluated using platinum electrodes since it is an inert material and consequently does not induce ion release in the electrolytic medium, facilitating DC mechanism comprehension, as previously registered in bacteria [Holandino et al, ; Gomes et al, ] and protozoa [Gomes et al, ] samples. The viability assays were performed by two methods: plating to quantify CFUs and propidium iodide (PI) incorporation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations